State Party Organizations, 1960-1980: (United States) - Cotter, Cornelius P. ([Verlag nicht ermittelbar], 1989)
This two-part data collection examines the complex role of party organizational strength in electoral politics. Major areas of inquiry were the conceptualization, measurement, and identification of the determinants and consequences of party organizational strength at state and county levels. Responses were gathered from mailed questionnaires and personal interviews with various state party officials. Part 1 contains data collected from former Republican and Democratic state party chairs (1960-1978) in the 27 sample states of the data collection. In addition, questionnaires were sent to current state party chairs (1978-1980) in nonsample states. Topics covered include: the factors and motives leading the respondent to seek and accept the chairmanship, budgetary data for typical election and non-election years, an assessment of the state party organization's relationship with county party organizations, and the frequency of the state party's dealings with the National Committee on party matters such as fund-raising, gaining assistance for state candidates, and federal appointments and patronage. Part 2 contains results from personal interviews with both the current state party chairs (1978-1980) and the executive director for each party in the 27 sample states. As in Part 1, respondents were questioned on a variety of issues such as their party's relationship with the National Committee, an assessment of the most important aspects of their job as chairman, and the state party's role in recruiting and screening candidates for state and national positions. Additionally, the executive director for each party was asked a series of questions concerning the operation and strength of the party. Items in the series included a description of the party headquarters, services provided by the party such as public relations or issue research, and sources of funding.